Evidence that different regional sympathetic outflows vary in their sensitivity to the sympathoinhibitory actions of putative 5-HT1A and alpha 2-adrenoceptor agonists in anaesthetized cats. - Ramage, A. G. (1989)
1. An investigation was carried out to determine whether the centrally acting hypotensive drugs whose mechanisms of action are due either to activation of 5-HT1A receptors (flesinoxan, 8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) and urapidil--also an alpha 1-adrenoceptor antagonist) or to activation of alpha 2-adrenoceptors (clonidine and moxonidine) cause differential sympathoinhibition. 2. Cats were anaesthetized with alpha-chloralose and simultaneous recordings were made of whole cardiac, splanchnic and renal nerve activity, blood pressure and heart rate. Cumulative dose-response (i.v.) curves were constructed in separate experiments for the above hypotensive agents on these parameters. 3. Renal nerve activity was found to be more sensitive to the sympathoinhibitory action of flesinoxan and 8-OH-DPAT when compared with cardiac nerve activity, whereas the reverse was observed for clonidine and moxonidine, cardiac being more sensitive than renal nerve activity. Splanchnic nerve activity was similarly affected by all drugs. Furthermore at the highest dose, all drugs tended to cause complete inhibition in all regional sympathetic nerve outflows. 4. Urapidil differed from all the above hypotensive drugs in that it caused a similar degree of sympathoinhibition in all sympathetic outflows at all doses. It is suggested that this may be due to the ability of urapidil to block central alpha 1-adrenoceptors in addition to stimulation of 5-HT1A receptors.